"Helpin' Me Resist and Refuse:" Class-Consciousness and Preaching (Homiletic, 2011)
This paper examines how consciousness of class can inform one's preaching. It does this by focusing in three areas. First, it considers how consciousness of the class dynamics in church and society can inform one's strategy in preaching. Issues range from the incorporation of social analysis into preaching to avoiding the potential pitfalls of class-based stereotypes and paternalism. Second, it considers how class-consciousness can affect the preacher's approach to biblical texts. For example, there are distinct challenges that arise when comparing economic orders of the biblical era with those of today. Third, it considers how class-consciousness can affect the development and articulation of theology. In the public sphere, it is important to assess who is speaking publicly about God and how they are speaking about God in relation to the lives of working class peoples. Ultimately, the essay concludes that class-consciousness could revolutionize the content of preaching in churches today in a manner analogous to that of the shift to gender-inclusive language.